Consideraciones para una actualización del concepto de totalidad social con base en la obra de Georg Lukács. - Nahuel Alzu, Alejandro (Revista Estudios de Filosofía)
In this paper I revisit the different elaborations of the concept of social totality that we can find through various moments of the work of the Marxist philosopher Georg Lukács, focusing on the understanding of the praxis of social agents tied to each of them. I begin with the analysis of this concept in his youth works and then I highlight a radical change of view between the characterizations found in History and class consciousness and Ontology of social being. My argument is that this reconsideration is associated with the theoretical necessity of conceiving a subjective praxis that could avoid alienation, as it seems to occur in the theoretical model of Lukács' youth work. Finally, I conclude that this new conception of the social totality enables a new kind of emancipatory praxis, far from the party dogmatisms that typify a great part of the twentieth century socialism.